A Fuzzy Qualitative Simulation Study of College Student’s Mental Health Status - Xiying Deng (Discrete Dynamics in Nature and Society)
The fuzzy qualitative approach used in this paper provides an in-depth study and analysis of the simulation of the mental health state of college students, which is continued from another perspective using structural equation modeling, in which sufficient conditions for the equation to satisfy local asymptotic stability, instability, and global attraction at the zero equilibrium point and sufficient conditions for the existence and instability of nonzero equilibrium points are discussed, respectively. In addition, the paper proves the boundedness of the solutions of the equation by mathematical induction and obtains sufficient conditions to ensure that the solutions are bounded. The intrinsic causes of college students’ psychological problems lie in the lack of social support in the family and outside the family and the influence of the overall social environment on college students. Finally, this paper puts forward some suggestions and countermeasures based on this research finding from three levels: family, school, and society, giving full play to the role of family support; schools should expand the main body of support, enrich the form of support, and provide comprehensive and multifaceted social support for college students. Finally, the simulation of the equation is carried out to verify the correctness of its conclusion. The rate of mental subhealth is 1.605 times that of college students admitted to ideal universities, which is consistent with our actual situation. At the level of condition guarantee, the hardware facilities, management system, and professional team of mental health education for college students are evaluated; from the specific content, the teaching work, educational activities, psychological counseling, and crisis intervention of mental health education for college students are evaluated; from the perspective of effect, the degree of goal achievement, social adaptation, and result satisfaction of the effect of mental health education for college students are evaluated. The final part analyzes and elaborates on the construction of evaluation indexes of mental health education for college students, the design of weight of guiding indexes, and the content and optimization path of the evaluation test. The results of the study show that personal ability and external pressure are important factors influencing college students’ mental health, and the influence of external pressure is greater. Logistic regression and structural equation modeling methods complement each other, and the findings of structural equation modeling are more comprehensive and integrated, while logistic regression illustrates the degree of each influencing factor.